MANTRA UNTUK PENYEMBUHAN DALAM TRADISI SUKU OSING BANYUWANGI - Novia Luthviatin (Universitas Jember, 2015)
Most Indonesian people use traditional medication to prevent and cure the disease. Mantra is a part of tradition and healing which practiced by Osing Tribe in Banyuwangi. This study aimed to explore how the traditional healers use mantra for healing in traditional medication in Osing tribe. This study used a qualitative approach of phenomenology with depth interviews, participatory observation, documentary materials and browsing the internet material. This study located in 4 traditional village, involves five (5) informants. Mantra is combined with massage,rajah, giving herbs and water, and attaching tools. The time required in a relatively short treatment is 15-20 minutes, while the time it takes patients to recover is one day to a week. The conclusion that mantra is used by Osing Tribe in Banyuwangi to cure the disease. Keywords: mantra, healing, Osing Tribe